The relationship between lean maturity and sustainable lean transformation gains with mediating effects of leadership and culture in Malaysia manufacturing sector - Azim Azuan, Osman (2022)
Toyota Motor’s survival during the 1973 global oil crisis, has inspired US manufacturers to transform from the mass production system to the lean production system. However, lean transformation attempted by most manufacturers around the globe has produced mixed results. Nearly two-thirds of the lean transformation ended in failure, while only a small percentage of those transformed have successfully sustained its gains. Therefore, this study empirically investigated the factors that contribute to Malaysian manufacturers’ ability to achieve sustainable gains as a result of their lean transformation initiatives. Based on extensive literature review, a multiple mediator’s research model was proposed to explain the relationship between lean transformation and sustainable gains. To address several gaps in the current knowledge, sustainable gains were operationalised from tangible and intangible gain facets. Besides that, maturity criteria (completeness, extensiveness and experience) in applying lean tools were used as proxies to measure the lean transformation level which served as the independent variable. Meanwhile, lean leadership and lean culture were proposed as mediators. The research model was underpinned by the integration of Theory E and Theory O, as well as the sustainable organisational concept. For testing the research model, a survey on 92 lean manufacturing organisations was conducted. The collected data was then analysed using the PLS-SEM technique running on SmartPLS 3.3.3 software. The results revealed that both lean leadership and lean culture fully mediated the relationship between lean tools adoption maturity and sustainable gains at β = 0.176, t = 2.397, p = 0.017 and β = 0.120, t = 2.016, p = 0.044 respectively. Thus, this study contributed to the lean management body of knowledge by providing tangible statistical evidence on previously unexplained relationship between lean maturity, lean leadership and lean culture with sustainable gains.